School pathways and economic practices of Portuguese Ciganos: some continuities and changes - Mendes, M. M. (2016)
The main aim of this article is to offer a comprehensive perspective to a better understanding of the actual situation of Portuguese Ciganos.1 In Portugal, the lack of recognition of Ciganos (Roma) and the sometimes incorrect ‘knowledge’ about them which are reflected in images that are limitative and distorted, suggest inferiority and are full of disdain, all of which negatively affects and restricts the life of Ciganos persons. This article intends to presents some of the main results of two qualitative studies conducted between 2004–2010, one of which sought to get to know Ciganos’ representations of domains, practices and situations perceived as discriminatory, while the other looked at the social integration paths of these persons. These studies produce new knowledge about both individual academic and occupational trajectories, and some of the main intergenerational changes that have occurred among Portuguese Ciganos. In addition, the article offers a new view about some social policies in Portugal and its impacts on Ciganos singularities. In fact, it’s possible to conclude that the universalism of the national social policies has not produced the desired effects in terms of a reduction in levels of poverty, exclusion, discrimination among Portuguese Ciganos.